Private Costs and Public Infrastructure : The Mexican Case - Murphy, Russell; Feltenstein, Andrew (Washington, D.C. : International Monetary Fund, 2001)
One objective of government investment is to develop public infrastructure which may reduce private sector costs. In a developing economy, the scope for payoffs to investments of this sort may be particularly large. A major concern related to the recent fiscal adjustment in Mexico is that it has been carried out, in part, by depleting public infrastructure stocks.We estimate the effects of public infrastructure on private sector costs in Mexico and calculate the implied optimal infrastructure stocks. Our estimates indicate that previous results suggesting a large productive role of public infrastructure capital are not robust. There is little evidence that public infrastructure plays a large role in reducing private sector costs.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet